2022
DOI: 10.1042/bst20220271
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 in immune signalling

Abstract: Extracellular signal-related kinases 1 and 2 (ERK1/2) are the final components of the mitogen-activated protein kinase (MAPK) phosphorylation cascade, an integral module in a diverse array of signalling pathways for shaping cell behaviour and fate. More recently, studies have shown that ERK1/2 plays an essential role downstream of immune receptors to elicit inflammatory gene expression in response to infection and cell or tissue damage. Much of this work has studied ERK1/2 activation in Toll-like receptor (TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 115 publications
0
24
0
Order By: Relevance
“…SELP is a type of cell adhesion molecule that is expressed on the surface of stimulated endothelial cells and activated platelets; SELP can mediate the interaction between leukocytes and endothelial cells, allowing leukocytes to “roll” along the surface of the endothelium, which is important for the recruitment of leukocytes to sites of inflammation (M. Chen & Geng, 2006). MAPK3 plays a key role in regulating various cellular processes, including cell proliferation, differentiation, and survival and has been shown to be upregulated in immune cells during inflammation, and its activation also is associated with the production of pro-inflammatory mediators, such as cytokines and chemokines (Lucas et al, 2022). In inflammation, VEGFA is important for recruiting of immune cells to the site of inflammation, forming of new blood vessels, maintaining the integrity of blood vessels, wound healing, and the development of the placenta during pregnancy; however, excessive, or uncontrolled production of VEGFA can contribute to the development of certain diseases, such as cancer (Scaldaferri et al, 2009; Shaik-Dasthagirisaheb et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…SELP is a type of cell adhesion molecule that is expressed on the surface of stimulated endothelial cells and activated platelets; SELP can mediate the interaction between leukocytes and endothelial cells, allowing leukocytes to “roll” along the surface of the endothelium, which is important for the recruitment of leukocytes to sites of inflammation (M. Chen & Geng, 2006). MAPK3 plays a key role in regulating various cellular processes, including cell proliferation, differentiation, and survival and has been shown to be upregulated in immune cells during inflammation, and its activation also is associated with the production of pro-inflammatory mediators, such as cytokines and chemokines (Lucas et al, 2022). In inflammation, VEGFA is important for recruiting of immune cells to the site of inflammation, forming of new blood vessels, maintaining the integrity of blood vessels, wound healing, and the development of the placenta during pregnancy; however, excessive, or uncontrolled production of VEGFA can contribute to the development of certain diseases, such as cancer (Scaldaferri et al, 2009; Shaik-Dasthagirisaheb et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of ERK1/2 is related to the activation of inflammatory response in the immune process. ERK1/2 are two very similar extracellular signal-regulated kinases in the MAPK family . The phosphorylation of ERK1/2 is related to the activation of inflammatory response in the immune process.…”
Section: Resultsmentioning
confidence: 99%
“…ERK1/2 are two very similar extracellular signal-regulated kinases in the MAPK family. 49 The phosphorylation of ERK1/2 is related to the activation of inflammatory response in the immune process. For example, Mycobacterium tuberculosis leads to immune evasion by inhibiting ERK1/2 phosphorylation in antigen-presenting cells, resulting in decreased IL-6 secretion.…”
Section: T-155mentioning
confidence: 99%
“…Phosphorylation of ERK1/2 is a critical step in promoting G1 to S transition and upregulating cell proliferation [ 25 ]. ERK1/2 signaling is also involved in the immune response [ 26 ]. We found that phospho-ERK1/2 was significantly upregulated in WT podocytes compared to KO podocytes 10 minutes after treatment with ICs.…”
Section: Resultsmentioning
confidence: 99%
“…Both the Akt and ERK1/2 pathways have been shown to be involved in signaling and lysosomal activation or antigen presentation after an immune challenge [ 24 , 26 , 36 ]. Our findings that KO podocytes showed little or no increase in phospho-Akt or phospho-ERK1/2 expression compared to baseline after treatment with ICs whereas WT podocytes had increased expression of these signaling mediators after IC treatment support the hypothesis that FcRn-mediated trafficking of immune complexes in podocytes modulates the podocyte response to immune stimuli and that lack of FcRn dampens the response to an immune insult resulting in less metabolically active and less immunogenic lysosomes.…”
Section: Discussionmentioning
confidence: 99%